A broad-spectrum virus- and host-targeting peptide against respiratory viruses including influenza virus and SARS-CoV-2 (2020)
The 2019 novel respiratory virus (SARS-CoV-2) causes COVID-19 with rapid global socioeconomic disruptions and disease burden to healthcare. The COVID-19 and previous emerging virus outbreaks highlight the urgent need for broad-spectrum antivirals. Here, we show that a defensin-like peptide P9R exhibited potent antiviral activity against pH-dependent viruses that require endosomal acidification for virus infection, including the enveloped pandemic A(H1N1)pdm09 virus, avian influenza A(H7N9) virus, coronaviruses (SARS-CoV-2, MERS-CoV and SARS-CoV), and the non-enveloped rhinovirus. P9R can significantly protect mice from lethal challenge by A(H1N1)pdm09 virus and shows low possibility to cause drug-resistant virus. Mechanistic studies indicate that the antiviral activity of P9R depends on the direct binding to viruses and the inhibition of virus-host endosomal acidification, which provides a proof of concept that virus-binding alkaline peptides can broadly inhibit pH-dependent viruses. These results suggest that the dual-functional virus- and host-targeting P9R can be a promising candidate for combating pH-dependent respiratory viruses.